Determination of epigallocatechin‐3‐gallate with a high‐efficiency electrochemical sensor based on a molecularly imprinted poly(o‐phenylenediamine) film. Issue 5 (12th February 2013) - Duan, Yuqing; Luo, Xiaoping; Qin, Yu; Zhang, Haihui; Sun, Guibo; Sun, Xiaobo; Yan, Yongsheng
Abstract An electrochemical molecularly imprinted polymer (MIP) sensor for detecting the existence of epigallocatechin‐3‐gallate (EGCG) in tea and its products was successfully developed on the basis of a glassy carbon electrode modified with an electropolymerized nonconducting poly(o‐phenylenediamine) film. The properties of the electrode were characterized by cyclic voltammetry, differential pulse voltammetry, and infrared spectroscopy. The template molecules could be rapidly and thoroughly removed by methanol/acetic acid. The linear response range for EGCG was 5.0 × 10−7–1.0 × 10−4 mol/L, and the limit of detection was as low as 1.6 × 10−7 mol/L. The prepared MIP sensor could discriminate between EGCG and its analogs. In addition, satisfactory results were obtained in the detection of real tea samples. The results of our investigation indicate that the MIP sensor was useful for the determination of EGCG with excellent selectivity, high sensitivity, repeatability, and reproducibility. This MIP sensor provides the potential for monitoring the variation of EGCG content during the industrial processes and for predicting the quality of tea and its products. © 2013 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013